Was Mill a Noncognitivist?. Issue 2 (3rd June 2013) - Macleod, Christopher
Abstract In this paper, I examine the presumption that Mill endorses a form of metaethical noncognitivism. I argue that the evidence traditionally cited for this interpretation is not convincing and suggest that we should instead remain open to a cognitivist reading. I begin by laying out the "received view" of Mill on the status of practical norms, as given by Alan Ryan in the 1970s. I then argue that there is no firm textual evidence for this reading of Mill: his remarks on "art" and "science" do not show the metaethical commitments they have been taken to. Neither is there firm textual evidence for a cognitivist reading. However, a noncognitivist interpretation suffers from the fault of anachronism and is difficult to reconcile with the clear commitment in Utilitarianism to the possibility of evidence being given for the desirability of pleasure. A cognitivist reading would not suffer from these faults, and on that basis, I conclude that we should think further about what a cognitivist reading of Mill might amount to.